Feasibility and Acceptability of a Reiki Intervention With Very Young Children Receiving Palliative Care. Issue 6 (November 2021) - Thrane, Susan E.; Grossoehme, Daniel H.; Tan, Alai; Shaner, Valerie; Friebert, Sarah
Abstract : Background: Very little research has been reported examining nonpharmacological symptom management strategies for very young, hospitalized children receiving palliative care, and none has involved Reiki—a light touch therapy. Objectives: The aim of this study was to determine if completing a Reiki intervention with hospitalized 1- to 5-year-old children with chronic, life-limiting conditions receiving palliative care was feasible and acceptable. Methods: Children ages 1–5 years receiving palliative care who were expected to be hospitalized for at least 3 weeks were recruited for a single-arm, mixed-methods, quasi-experimental pre- and poststudy. Six protocolized Reiki sessions were conducted over 3 weeks. We calculated feasibility by the percentage of families enrolled in the study and acceptability by the percentage of families who completed all measures and five out of six Reiki sessions. Measures were collected at baseline, at the end of the intervention period, and 3 weeks later. At the final follow-up visit, parents were verbally asked questions relating to the acceptability of the intervention in a short structured interview. Results: We screened 90 families, approached 31 families, and recruited 16 families, whereas 15 families declined. Reasons for not participating included that the child had "a lot going on, " would be discharged soon, and families were overwhelmed. Of those enrolled, most completed all measures at three time points and five out of six Reiki sessions. We completed nearly all scheduled Reiki sessions for families that finished the study. All parents reported that they would continue the Reiki if they could, and almost all said they would participate in the study again; only one parent was unsure. Discussion: Young children and their parents found Reiki acceptable; these results are comparable to an earlier study of children 7–16 years of age receiving palliative care at home and a study of massage for symptom management for hospitalized children with cancer. These findings add to the literature and support further investigation of Reiki's efficacy as a nonpharmacological symptom management intervention.